Digitalisasi Sistem Administrasi Perpajakan: Pendekatan TAM (Technology Acceptance Model) - Nurul Ainun Nafisah; Ulfa Puspa Wanti Widodo (CV. KAMPUSA AKADEMIK PUBLISING, 2024)
The aim of this research is to find out about the digitalization of the tax administration system using e-bupot seen from several aspects of the TAM (Technology Acceptance Model) approach at PT.X Gresik.The research method used is descriptive qualitative research.The data in this research was obtained by interviews with users and through literature studies.The results of this research show that based on the TAM theory which is seen from the aspects of convenience,usability, attitude of use, tendency to use,and actual conditions of use, the existence of the e-bupot application is felt to be quite easy and helpful for users in completing their work such as making proof of withholding, posting and tax reporting. Despite the usefulness that users feel in using the e-bupot, in fact there are still problems that often occur,such as delays in the posting process,so there is a need to improve the management of the e-bupot system.